2016
DOI: 10.1002/jcb.25526
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Induces Oxidative Stress Through Activation of NADPH Oxidase in Renal Tubular Cells: Antioxidant Effect of L‐Carnitine

Abstract: Leptin is a protein involved in the regulation of food intake and in the immune and inflammatory responses, among other functions. Evidences demonstrate that obesity is directly associated with high levels of leptin, suggesting that leptin may directly link obesity with the elevated cardiovascular and renal risk associated with increased body weight. Adverse effects of leptin include oxidative stress mediated by activation of NADPH oxidase. The aim of this study was to evaluate the effect of L-carnitine (LC) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…The current experiment was consistent with that of Shabani et al (2015), which revealed that reduced leptin is associated with decrease in blood glucose (26). Recent evidence suggests that leptin can stimulate ROS excessive formation through increase in nicotinamide adenine dinucleotide phosphateoxidase (NADPH) oxidase activation (27). Inflammation is the common basis for various diseases, and leptin contributes to the increase inflammatory cytokines (28,29).…”
Section: Discussionsupporting
confidence: 89%
“…The current experiment was consistent with that of Shabani et al (2015), which revealed that reduced leptin is associated with decrease in blood glucose (26). Recent evidence suggests that leptin can stimulate ROS excessive formation through increase in nicotinamide adenine dinucleotide phosphateoxidase (NADPH) oxidase activation (27). Inflammation is the common basis for various diseases, and leptin contributes to the increase inflammatory cytokines (28,29).…”
Section: Discussionsupporting
confidence: 89%
“…However, the relationship between leptin and oxidative stress has not been fully elucidated. Leptin stimulates in vitro ROS production in different cell types 40, 41 and systemic oxidative stress in animal models 42 , suggesting a stimulatory role of leptin. On the contrary, oxidative stress is increased in obese Zucker fa/fa rats 39 , while leptin administration reduces the oxidative stress in different cellular 43 or rodent models 44, 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, insulin improves glucose utilization in the adipocytes of elderly subjects with DKA to further stimulate leptin secretion. 35 Leptin in the diabetic endothelial cells significantly increases intracellular ROS. In addition, DKA can be reversed by reducing HPAmediated systemic lipolysis and hepatic gluconeogenesis and ketogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…Leptin induces ROS production by activating protein kinase A to increase fatty acid oxidation 34 and by inducing NADPH oxidase activation-mediated oxidative stress. 35 Leptin in the diabetic endothelial cells significantly increases intracellular ROS. 14 The mechanism behind this observation may be related to leptin stimulating fatty acid oxidation in mitochondria and increasing free radical production.…”
Section: Discussionmentioning
confidence: 96%